Mobile Phone Innovation and Environmental Sustainability in Sub-Saharan Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2017)
This study investigates how the mobile phone can complement knowledge diffusion in order to influence CO2 emissions in 44 Sub-Saharan African countries for the period 2000-2012. The empirical evidence is based on Generalised Method of Moments. Three knowledge diffusion variables representing three of the four pillars of the World Bank's Knowledge Economy Index are employed: educational quality, information and communication technology (ICT) and scientific output. Six CO2 emission variables are used, namely: CO2 per capita, CO2 from electricity and heat, CO2 from liquid fuel, CO2 from manufacturing and construction, CO2 from transport and CO2 intensity. In the assessments, a decreasing tendency in these variables translates into positive conditions for environmental sustainability. Based on net effect from complementarities, the following findings are established. First, the mobile phone complements education to have a net negative effect on CO2 emissions per capita and CO2 emissions from the consumption of liquid fuel. Second, where some positive net effects of knowledge diffusion are apparent, corresponding marginal effects are negative. Corresponding mobile phone penetration thresholds at which the positive net effects on CO2 emissions can be dampened and reversed are largely within policy range. Practical and theoretical implications are discussed.
Keywords: C52; O38; O40; O55; P37; 330; CO2 emissions; ICT; Economic development; Africa